ANALISIS FAKTOR-FAKTOR PRODUKSI DALAM SISTEM AGROFORESTRI TERHADAP PRODUKTIVITAS KOPI ROBUSTA DI KABUPATEN BANYUWANGI - Widiastuti, Yusmia (Nusantara Hasana Journal, 2025)
This study was conducted in Gombengsari Village, Kalipuro District, Banyuwangi, which is known as a coffee producing area with many coffee farmers. The study was conducted using interview, questionnaire, and observation methods, and relied on primary and secondary data. To analyze the production factors that affect robusta coffee productivity, multiple linear regression analysis was used. The results showed that the number of workers (tcount 2.166; sig. 0.044), fertilizer use (tcount 3.073; sig. 0.007), and land area (tcount 5.269; sig. 0.000) had a significant effect on robusta coffee productivity. The F test showed that simultaneously, the three variables had a significant effect on robusta coffee productivity (Fcount 24.641; sig. 0.000). This indicates that these three factors together do play an important role in determining how much coffee harvest farmers can obtain.